2021
DOI: 10.1177/20533691211039151
|View full text |Cite
|
Sign up to set email alerts
|

Management of sleep disorders in the menopausal transition

Abstract: The menopausal transition is associated with increasing sleep disorders including sleep apnoea and restless leg syndrome. Insomnia is the most common and is recognised as a core symptom of the menopause. Guidelines to support decision making for women with sleep problems during the menopausal transition are lacking. Sleep problems are associated with negative impacts on healthcare utilisation, quality of life and work productivity. Sleep deprivation is a risk factor for cardiovascular disease, diabetes, obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…This period, and the postmenopausal stage that follows, are associated with a significant increase in sleep disturbances such as sleep apnea, insomnia and restless leg syndrome, all of which impact the quality of life, health, and social and personal functioning. 63 During perimenopause, insomnia is the most frequently experienced and treatable sleep disorder. 64 Effective treatment of pre-existing sleep problems can prevent the onset of psychotic thinking and can reduce symptom severity if diagnosed after the onset of psychosis 65 although this has not yet been specifically studied in DD.…”
Section: Community Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…This period, and the postmenopausal stage that follows, are associated with a significant increase in sleep disturbances such as sleep apnea, insomnia and restless leg syndrome, all of which impact the quality of life, health, and social and personal functioning. 63 During perimenopause, insomnia is the most frequently experienced and treatable sleep disorder. 64 Effective treatment of pre-existing sleep problems can prevent the onset of psychotic thinking and can reduce symptom severity if diagnosed after the onset of psychosis 65 although this has not yet been specifically studied in DD.…”
Section: Community Levelmentioning
confidence: 99%
“…Insomnia Insomnia can worsen DD symptoms. 62, 63 Rx of insomnia to improve outcome. 62 Sleep apnea (OSA) OSA can increase symptom severity esp.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Also, psychoneurological symptoms are shown in almost all women in the perimenopausal period. Ovarian hormones regulate cognitive and mood function ( Azizi-Malekabadi et al, 2015 ; Lozza-Fiacco et al, 2022 ; Schaedel et al, 2021 ; Shors and Leuner, 2003 ). 17β-estradiol (E 2 ) replacement exhibits anti-inflammatory properties in the CNS ( Brown et al, 2010 ).…”
Section: The Differential Effects Of Cytokines On Stress Responses In...mentioning
confidence: 99%
“…17β-estradiol (E 2 ) replacement exhibits anti-inflammatory properties in the CNS ( Brown et al, 2010 ). Some studies reported that mood disorders are related to change of neuroimmune systems ( Lozza-Fiacco et al, 2022 ; Schaedel et al, 2021 ). Also, psychological stress is related with proinflammatory cytokines in the brain such as IL-6, IL-1β, and TNF-α ( Buchanan et al, 2008 ).…”
Section: The Differential Effects Of Cytokines On Stress Responses In...mentioning
confidence: 99%
“…The menopausal transition and the postmenopausal period are associated with a significant increase in sleep disorders, such as sleep apnea, insomnia, and restless leg syndrome [ 24 ]. Insomnia is the sleep disorder most commonly found in women, and it has been associated with negative impacts on healthcare, quality of life, and functionality [ 25 ].…”
Section: Introductionmentioning
confidence: 99%